Sociodemographic and Clinical Characteristics of Persons with Epilepsy Attending an Epilepsy Clinic of a Tertiary Hospital in Bangladesh (Journal of Rangpur Medical College, 2024)
Background: Epilepsy is a common neurological disorder found in all societies. It is seen that the relative frequency of various clinically important characteristics is different in persons with epilepsy (PWE) living in different geographical areas. The purpose of this study was to describe the sociodemographic and clinical characteristics of a cohort of patients with epilepsy from an Epilepsy Clinic of a tertiary hospital in Bangladesh. Methods: This cross-sectional study was conducted in the Department of Neurology at Rangpur Medical College Hospital, Rangpur, Bangladesh, from July 2022 to June 2023. The patients were recruited from the epilepsy clinic. A structured questionnaire was designed to collect relevant information by interviewing the consecutive PWEs. Results: A total of 252 PWEs were recruited, of which 134(53.2%) were male. Most [200(79.4%)] of them were young (age group 0 to 29 years) and had generalized seizures 147(58.3%). The median age of the 1st seizure was 11 years (range 0.5-73.0), and the median duration of epilepsy was 5.0(0-35) years in the present study. EEG, CT scan, and MRI could be done in 200(79.4%), 128(50.8%), and 68(27%, respectively. Among them, 24.2%(61), 10.7%(27), and 11.1%(28) patients had different types of abnormalities on EEG, CT scan, and MRI, respectively. A family history of seizures was present in 20(7.9%) patients. Sixteen patients(6.3%) were not getting any AEDs, 63.1% and 30.6% were on single and multiple AEDs, respectively. Sixty-five (25.8%) patients reported stopping the drug without any medical consultation. Forgetfulness was the most reported (21, 33.8%) reason for stopping drugs, followed by the misconception that the disease was cured (14, 21.5%), lack of time to buy pills (12, 18.5%), and no money to buy (9, 13.8%). Seventy-seven reported having two or more continuous seizures despite taking AEDs regularly. Conclusions: Present study documented some treatment gap and non-adherence to medication in PWE. PWE should be adequately advised about the disease and the effects of drug non-compliance.J Rang Med Col. March 2024; Vol. 9, No. 1: 44-49